AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING DESCRIPTIVE TEXTS - Siti Nurfidoh; Evie Kareviati (IKIP Siliwangi, 2021)
The objective of this study is to find out the difficulties of writing descriptive text and what factors causing difficulties in writing descriptive text. This study involved 12 students in eighth grade of junior high school in Cipongkor. To obtain the data, three kinds of the research instruments were used, namely a writing test (Heaton, 1988), questionnaire and observation. The findings based on the writing test showed that the errors produced by the students were missordering with 33.6%, the punctuation 26.8%, the tenses 17.4%, wrong diction 12.1%, spelling 7.4%, and the last is prepositions 2.7%. Based on the questionnaire and observation, the factors caused students difficulties in writing descriptive text are lack of interest in learning English, the poor understanding of the generic structure of descriptive test, poor in grammar knowledge and use, and the low motivation in writing descriptive text. Keywords: Errors, Descriptive Text, Writing